Elderly mortality in Italian regions at the beginning of the health transition (1881-1921) - Lorenzo Del Panta (Statistica, 2013)
The paper aims to highlight and analyze possible regional patterns of mortality at advanced age (70-90 years) in Italy at the turn of the nineteenth century. The available data are referred to four distinct occasions, namely 1881-82, 1900-01, 1911-12 and 1921-22. After focusing attention on several elderly mortality indicators, we propose to analyze the resulting three-way array (with modes regionsindicatorsoccasions) using the STATIS method. As a critical preliminary step, new regional life tables for 1881-82 are constructed in order to reduce the possible bias due to the inaccuracy of the age distribution of the population and of the deaths in 1881. The resulting life tables are compared with Gini and Galvani’s ones and those available in the Human Mortality Database.